The Extension of the Village Head’s Term of Office in Law Number 3 of 2024: A Review from the Perspective of Siyāsah Dustūriyyah - Sakrina, Cut Putri; Rispalman, Rispalman; Umur, Azmil (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The passage of Law Number 3 of 2024 concerning Villages extends the term of office of the Village Head to eight years, with a maximum of two terms. This is similar to the term limits during the New Order era. However, in practice, elections are often delayed, resulting in the regulations regarding the term of office not always being implemented on schedule. This research aims to analyze the changes in the Village Head’s term of office in Law Number 3 of 2024 from the perspective of siyāsah dustūriyyah. Using a normative-juridical approach, the study finds that the extension of the term to eight years reflects efforts to ensure the stability of village governance and promote public welfare. However, it also necessitates the establishment of effective oversight mechanisms to prevent abuse of power. The extended term is expected to provide sufficient time for Village Heads to optimize development and improve the quality of public services. Nevertheless, this change must be accompanied by strict supervision and evaluation mechanisms to safeguard against authoritarian tendencies. Philosophically, this amendment reflects the values of justice and popular sovereignty; sociologically, it promotes village empowerment; and juridically, it ensures legal certainty. In the framework of siyāsah dustūriyyah, the leadership of the Village Head is not merely administrative but also a moral and spiritual trust that must be exercised with justice and responsibility in accordance with Islamic principles. Leadership remains valid only as long as it is exercised fairly and rightly, and must be replaced if it deviates from these values. Ultimately, the change in the Village Head’s term of office aligns with the principles of democracy, Islamic values, and the need to establish effective and just village governance.